Determining the effect of primer mismatches on quantitative PCR accuracy and developing guidance for design of primers with sequence variations - Ledeker, Brett Michael, author; De Long, Susan K., advisor; Omur-Ozbek, Pinar, committee member; Reardon, Kenneth F., committee member (Colorado State University. Libraries, 2012)
Although quantitative PCR (qPCR) is a powerful tool for investigating environmental systems, target gene sequences for organisms of interest often are not well known, which has resulted in few reliable primers for many applications. Additionally, the sequences of target genes found in diverse strains often contain sequence variations, and therefore, primer sets containing single or multiple primer-template mismatches are common. However, the detrimental impact of these mismatches on quantification accuracy and amplification efficiency has not been investigated thoroughly. Thus, the research objectives of this study were to elucidate the relationships between primer mismatches and the accuracy of qPCR assays and to develop guidance for designing primers targeting genes displaying sequence variations. The pcrA gene (encoding perchlorate reductase) from Dechloromonas agitata was used as a model system for this study, and a linearized plasmid containing the cloned pcrA gene was used as the qPCR template. A large number of pcrA primers (16 forward and 16 reverse) were designed containing from zero to three mismatches at various locations. Combinations of primers were tested to determine the impact of mismatches on the amplification efficiency, the threshold cycle (CT), and the quantification accuracy. Quantification accuracy was calculated as the percent detected by dividing the quantity measured with mismatch primers by the quantity measured with perfect match primers and multiplying by 100. Single mismatches at the 3' end resulted in quantification accuracies as low as ~3%, and single mismatches at the 5' end resulted in quantification accuracies as low as ~33%. Double and triple mismatches at the 5' resulted in quantification accuracies as low as ~17% and ~2%, respectively. Reductions in quantification accuracy correlated with increases in CT induced by mismatches but not with changes in amplification efficiency. Combining mismatched forward and reverse primers had an impact equivalent to the combined effect of the individual mismatch primers. Analogous qPCR tests were run with three other model genes: celS (encoding family 48 cellulase), C23O (encoding catechol dioxygenase, involved in toluene degradation), and hydA (encoding periplasmic hydrogenase, involved in fermentation). Primers were artificially designed to contain mismatches with these target genes, and results demonstrated that single or double mismatches can have a substantial detrimental impact on quantification accuracy in a broad range of systems. The results of this study indicate that caution must be taken to avoid mismatches when designing qPCR primers targeting genes with sequence variations and the findings serve to guide future design of primers for accurately quantifying genes in environmentally relevant systems.
Keywords: accuracy; mismatch; primer design; primers; qPCR; sequence variations